Development and application of a stepwise-assembled modular biomimetic lung chip for analyzing formaldehyde-induced cellular ferroptosis - Chen, Siyu; Li, Zezhi; Yan, Quanping; Hua, Chenfeng; Shang, Pingping; Liu, Kejian; Zhao, Junwei; Jin, Guangxiang; Li, Xiang; Xie, Fuwei (Frontiers in Bioengineering and Biotechnology, 2025)
Formaldehyde poses a significant threat to human health, yet its toxicity assessment is limited by current detection methods. This study developed a modular biomimetic lung chip which consists of gas concentration gradient generator module and cell culture module, assembled using alignment holes and micropillars. This design enables stepwise experimental procedures, including cell loading, gas concentration gradient exposure, and cell sample collection, through the assembly and disassembly of the modules. Using this chip to investigate the formaldehyde-induced cellular ferroptosis, BEAS-2B cells were exposed to formaldehyde under a concentration gradient. Transcriptomic sequencing revealed the effects of different formaldehyde concentrations on the expression of ferroptosis-related genes in cells, identifying 12 ferroptosis-related genes (FRGS) and an enhancement of oxidative stress. The ferroptosis inhibitor (deferoxamine mesylate) significantly reduced cell death and reactive oxygen species levels, confirming the involvement of ferroptosis in formaldehyde-induced toxicity. Furthermore, deferoxamine mesylate modulated the expression of hub genes of FRGS, including PTGS2, ATF3, CDKN1A, PLIN2, and DUOX1, at both transcript and protein levels. These findings provide novel insights into the molecular mechanisms underlying formaldehyde-induced respiratory damage and establish the modular biomimetic lung chip as a powerful platform for studying environmental toxicants.